Job Satisfaction among Healthcare Workers in Saudi Arabia: A Systematic Review - Sultan Ali Hussan al Gaflah; Abdullah Ali Saeed Al Nahdi; Yahya Muhammad Rajih Al Barqi; Mohammed Mana Alqahtani; Ohud Badday Alrashdi; Abdulwahab Shadad Mahyaa Alrashdi (International Journal of Medical Toxicology and Legal Medicine, 2024)
1. Introduction: Job satisfaction among health practitioners has been an area of interest for an extended period, as it plays an important foundation in the health system to deliver high-quality care services to patients. This study aims to examine the determinants of job satisfaction of healthcare workers in Saudi Arabia, as the health workforce is crucial within the health system. The health workforce consists of every person engaged in actions whose primary intent is to improve health, including medical doctors, nurses, and health managers. Since Vision 2030 was launched in Saudi Arabia, a reformed health system with a focus on the improvement of health services was anticipated; hence, the Saudi government put a lot of effort into assessing, monitoring, and providing care services through KPIs). Job satisfaction of health practitioners is considered an essential factor that affects their efficiency, well-being, and mental health. In addition, it is also a significant aspect that affects the intention to leave the job, and the changes of the workforce have the potential to drastically affect the capacity of the health system. A multistage sampling method was employed to obtain a sample size of 590 health workers from 25 hospitals. The results show that males were significantly more satisfied than females in relation to specialty, organization, and the overall global score. Older health practitioners have a higher level of satisfaction than younger ones in areas such as salary, working conditions, social recognition, and organizational structure. Saudi health practitioners were less satisfied in all aspects, while the non-Saudi (Arab) healthcare practitioners were the most satisfied in all aspects except city happiness. Medicine and surgery practitioners were the most satisfied professionals in all score aspects. Dental healthcare workers were the least satisfied professionals in all overall global score aspects. Health practitioners with more than five years of experience were significantly the most satisfied in all aspects except working environment. Methods: A literature search was conducted using the following databases. The eligibility criteria were as follows: a) full articles, b) articles written in English, c) only in Saudi Arabia, and d) research focused on job satisfaction. The retrieval was completed on 30th March 2021. A good quality study retrieval form and data extraction form were used to assist. A combination of Medical Subject Headings (MeSH) and the Arabic terminology was used as the searched terms. “Job satisfaction in SaudiGCC countries or Middle East countries” was used as a common MeSH term. Conclusion: Conclusion The current systematic review found that only hospital type indicates significant variability between studies, so cross-sectional studies should be interpreted with caution. There is a relatively high prevalence rate in burnout dimensions between Saudi healthcare providers, especially with low and moderate quality studies. Future research is recommended to include large samples among health care workers in different regions to better support and understand the different characteristics of each region. Healthcare workers should consider screening for burnout, such as a short or more sophisticated scale after further evaluation. The proportion of burnout prevalence is high and changes in this era may indicate a high level of stress, which is expected. As well as providing tangible help or funding, health workers should be supported with detailed guidance, which has been implemented in other countries and has repeatedly shown to be one of the most effective interventions. Education, work environment, and job satisfaction have been suggested for further research. More research, including adjustment variables and using better quality methods, is needed to better understand how it affects burnout. Prospective and meta-control studies are required for this. (Aiman Halawani et al., 2021)